Analysis of Social Media Strategy on Behavioral Changes: A Case Study of Dilans Indonesia Organization - Elfryda Amelia Dhamayanti; Yuliani Rachma Putri (Publikasi Indonesia, 2025)
Digital media access is crucial for the disabled and elderly, but access gaps limit their participation. Dilans Indonesia seeks to empower and fight for their rights through social media. This research aims to analyze the strategies implemented through Dilans Indonesia's social media aimed at achieving changes in public behavior. The initiative of the establishment of Dilans Indonesia is to empower individuals with disabilities and the elderly to become empowered and independent communities while advocating the voices of the disabled and elderly community to the government. This research uses a qualitative research method with a case study approach, which is analyzed through data processing using NVivo software. The research findings show that social media activities carried out by Dilans Indonesia in promoting a culture of inclusive living have created changes in individual perspectives and behaviors towards disability issues as well as increased visibility and involvement of the disabled and elderly community. The continuity in the delivery of the message campaign is in line with the social marketing strategy applied, with the aim of raising awareness, expanding understanding, and changing people's perspectives, attitudes and behaviors towards people with disabilities and the elderly.